Perception of students in public schools about recycling: tools of initiation environmental education - Teixeira, Robson da Silva; Souza, Rodrigo Otavio Lopes de; Vasconcellos, Carlos Alexandre Bastos de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This study intends to disseminate environmental education in students from elementary education at public schools in the Rio de Janeiro city, seeking them aware of environmental issues around the selective collection and recycling of these materials. An educational materials as a tool for introduction to environmental education was prepared. It consists of a primer on paper recycling based on the information given by the students themselves and even a recycling workshop where students can experience the practical of recycling materials. At the end of this study a survey aimed at examining the degree of acceptance of training and the possible replication of the knowledge acquired was performed. The analyzed data showed that 100% of the students liked to have participated in the paper recycling workshop and the students believe that they can play it at home, using the educational material provided. Thus, it was concluded that the material proposed is to encourage students from public schools in Rio de Janeiro the practice of environmental education, forming multipliers to the consolidation of the sustainability process.